2013
DOI: 10.1155/2013/315387
|View full text |Cite
|
Sign up to set email alerts
|

Building Spinal and Brain Commissures: Axon Guidance at the Midline

Abstract: Commissural circuits are brain and spinal cord connections which interconnect the two sides of the central nervous system (CNS). They play essential roles in brain and spinal cord processing, ensuring left-right coordination and synchronization of information and commands. During the formation of neuronal circuits, all commissural neurons of the central nervous system must accomplish a common task, which is to project their axon onto the other side of the nervous system, across the midline that delineates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 146 publications
(204 reference statements)
0
6
0
Order By: Relevance
“…Chemotaxis is characterized by the directed movement of cells along a chemotactic gradient and is crucial for many biological processes, including neuronal patterning ( Castellani, 2013 ), wound healing ( Andasari et al, 2018 ), immune response ( Kolaczkowska and Kubes, 2013 ), and cancer metastasis ( Stephens et al, 2008 ; Polacheck et al, 2013 ). Even apart from its significant biological function, chemotaxis is an invaluable system for understanding intracellular signaling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotaxis is characterized by the directed movement of cells along a chemotactic gradient and is crucial for many biological processes, including neuronal patterning ( Castellani, 2013 ), wound healing ( Andasari et al, 2018 ), immune response ( Kolaczkowska and Kubes, 2013 ), and cancer metastasis ( Stephens et al, 2008 ; Polacheck et al, 2013 ). Even apart from its significant biological function, chemotaxis is an invaluable system for understanding intracellular signaling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…One way to ensure proper circuit formation is through precise control of extending growth cone velocities. Previous studies have shown that regulation of velocity can be achieved through external signals, such as neurotransmitters and morphogens (Castellani, 2013;Petros et al, 2008). However, the degree to which neurons autonomously regulate their velocity is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In bilateral organisms, multiple reciprocal neuronal projections interconnect the 2 halves of the central nervous system (CNS), forming a dense network of commissures that allow integration and coordination of left-right neuronal activities 9,36 . During embryonic and early postnatal developmental periods, commissural axons navigate through the central midline at all axial levels, crossing from one side of the CNS to the other one at specific time points and positions 9 .…”
Section: Introduction To the Semaphorin Familymentioning
confidence: 99%
“…During embryonic and early postnatal developmental periods, commissural axons navigate through the central midline at all axial levels, crossing from one side of the CNS to the other one at specific time points and positions 9 . Commissural axons can be surrounded by or mixed with ipsilateral axons that are committed to build circuits between neurons of the same side, and that never cross the midline.…”
Section: Introduction To the Semaphorin Familymentioning
confidence: 99%
See 1 more Smart Citation